Spraying Disinfectants to Combat SARS-CoV-2 Transmission: Is it Fruitless Rather Than Fruitful? (Bangladesh Journal of Infectious Diseases, 2021)
Abstract not availableBangladesh Journal of Infectious Diseases 2020;7(2):113-114